Natural Dyes Characterization of Local Plants as Acid-Base Indicator - Nelly Dayanti; Silpia Vilda Saputri; Arit Arit; Rini Muharini; Masriani Masriani (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
Hanjuang, mangosteen, putat, and tabelian plants are used by people of Lanjak deras Village as natural dyes for woven cloth and food so that they can be used as an alternative substitute synthesis indicators that are limited in a remote area. The purpose of the study is to determine the best type of solvent in extracting the samples, pH range, UV spectrum profiles, precision, and accuracy of the plant's extract as indicator. The sample was the plants that are used by the people of West Borneo as natural dyes, namely putat flower, tebelian stem, mangosteen leave, and hanjuang leave. Each sample was macerated with four types of solvents, namely aquadest, ethanol, methanol, and (1:1) ethanol:methanol, then the extract was testing by pH range. The extracts providing color changes were determined for its UV-Vis spectrum profile, stability, accuracy, and precision. The results showed that ethanol and methanol were suitable for extracting mangosteen leaves, methanol for putat flowers, ethanol for hanjuang leaves, and (1: 1) ethanol:methanol for tebelian stems. Mangosteen leaf extract, putat flower, and tebelian stem gave a pH range of 12-14, while hanjuang leaf extract did not change color. The phytochemical test results and UV spectrum profile of mangosteen leaf extract, putat flower, and tebelian stem indicated the presence of phenolic compounds. The powder and extract solution had high stability. Mangosteen leaf extract, putat flower, and tebelian stem had precision and accuracy with the medium category. These data indicated that mangosteen leaf extract, putat flower, and tebelian stem have potential as indicators of acid-base.